2021
DOI: 10.1111/aab.12699
|View full text |Cite
|
Sign up to set email alerts
|

Development of mycoinsecticide formulations with Beauveria bassiana and Metarhizium brunneum for the control of Orosanga japonica (Hemiptera: Ricaniidae)

Abstract: Entomopathogenic fungi are promising microbial agents for agricultural pests, especially piercing-sucking insects. In this study, eight indigenous fungal isolates including four isolates of Metarhizium brunneum and four isolates of Beauveria bassiana were tested on Orosanga japonica Melichar (Hemiptera: Ricaniidae) in order to find an effective control agent that can be utilised for the development of oil-based fungal mycoinsecticides. In the screening test using 1 Â 10 7 spores ml À1 concentration, KTU-24 (B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…A group of scientists from Karadeniz Technical University analysed the effect of Bacillus thuringiensis on individuals of the cicada family, namely Orosanga japonica, and managed to find an insecticide concentration that caused mortality of more than 97% of pests (Biryol et al, 2021). However, in this study, such results were not achieved even when combining the treatment of crops with Bacillus thuringiensis and pyrethrum.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A group of scientists from Karadeniz Technical University analysed the effect of Bacillus thuringiensis on individuals of the cicada family, namely Orosanga japonica, and managed to find an insecticide concentration that caused mortality of more than 97% of pests (Biryol et al, 2021). However, in this study, such results were not achieved even when combining the treatment of crops with Bacillus thuringiensis and pyrethrum.…”
Section: Discussionmentioning
confidence: 81%
“…The concentration of Bacillus thuringiensis was selected based on the analysis of previous studies ( Shahini et al, 2021). Following the experiments, the use of entomopathogenic fungi contributes to 58% to 98% of insect mortality (Biryol et al, 2021), most often used to control aphids or whiteflies that can damage the stems and leaves of cabbage, which further affects the yield of the crop (Khun et al, 2021). Additional treatment with a pyrethrin solution was supposed to increase the efficiency of Bacillus thuringiensis.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%
“…As in this study, EPF isolated from a particular host or soil have shown to be virulent to other hosts. Biryol et al (2021b) reported that soil originated M. anisopliae (KTU-51) isolate showed 100% mortality on Orosanga japonica Melichar (Hemiptera: Ricaniidae). Since L. occidentalis is known to accumulate for overwintering in many different places, e.g., under loose bark, in holes of dead logs, or in bird nests, conidial transmission among adults may be possible during this time.…”
Section: Discussionmentioning
confidence: 99%
“…EPF infections are not limited to chewing insects, as they are not required to be ingested or eaten. They are unique in controlling insect pests that feed by sucking plant or animal juices (Lacey and Goettel 1995;Biryol et al 2021;Eski et al 2022). Despite all of the control methods, strategies and agents, the aphid species continue to be a major agricultural and horticultural pest, and their harm is gradually increasing.…”
Section: Introductionmentioning
confidence: 99%